Mengelola Bisnis Syariah bagi Enterpreneur Muslim - Muslihun; Sanurdi; Zakiah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Sharia-based business is a business activity from processing to selling products in order to gain profits based on sharia. The aim of this paper is to briefly understand the concept of managing sharia business for Muslim Entrepreneurs. The method used is a literature study where researchers collect data through documentation and literature. Researchers' data analysis techniques rely on books, journals and articles as part of data analysis or interpretation by collecting notes on research findings which are presented in a systematic manner after first carrying out data reduction or data selection. The results obtained show that Muslim entrepreneurs should have good behavior, such as acting friendly towards consumers. Behaving well by implementing polite and courteous behavior will make consumers comfortable and happy. Trust is also a behavior that Muslim entrepreneurs must have in doing business. Rasulluah Saw is an example of an honest businessman because of his trustworthy nature. The concept of Islamic business management contains elements and principles that must be implemented in organizing, the elements are; Planning, Organization, Coordination, Controlling, and Leading. At the level of sharia-based business management practices, a Muslim entrepreneur should have the abilities, namely; First, producing business products must be halal; Second, the Al-Quran and Hadith as the basis for business management; Third, don't make false promises and overpromise in business; Fourth, have business intentions and contracts adhering to Islamic sharia principles.